Needs Analysis in Program Development - Erdoğan, Polat; Güler, Gülay (My University, 2017)
The needs analysis, which is used in the field of education and is considered as the first and most effective step for the program development, has a great proposition in contemporary and real education. Especially during the last two decades, it has been used by many educational institutions in the assessment of educational needs. Because of its widespread use and increased prevalence, this study's purpose is to explain the needs analysis in program development with its different dimensions and holistic reality. This research is a qualitative study based on the descriptive analysis of the documents that are obtained by using the snowball sampling technique. In the current research, efforts to provide validity and reliability were tried to be carried out objectively, colleague confirmation was taken and expert examination was carried out. In the research, the definition, history, purpose, approaches, types, techniques and stages of needs analysis are explained. In the research, it has been reached that needs assessment is not a matter of preference but a necessity. That is why it is necessary to critically focus on needs analysis in program development. A number of suggestions are presented considering the importance of this topic
Keywords: Education; Needs analysis; Program development